The risk of financial intermediaries - Delis, Manthos D.; Hasan, Iftekhar; Tsionas, Efthymios G. (Journal of Banking & Finance, 2014)
This paper reconsiders the formal estimation of bank risk using the variability of the profit function. In our model, point estimates of the variability of profits are derived from a model where this variability is endogenous to other bank characteristics, such as capital and liquidity. We estimate the new model on the entire panel of US banks, spanning the period 1985q1–2012q4. The findings show that bank risk was fairly stable up to 2001 and accelerated quickly thereafter up to 2007. We also establish that the risk of the relatively large banks and banks that failed in the subprime crisis is higher than the industry’s average. Thus, we provide a new leading indicator, which is able to forecast future solvency problems of banks.